Synthesis of 5,7-dimethyl-[1,2,4]triazolo[1,5-a]pyrimidine-2-thiol and derivatives via (4,6-dimethylpyrimidin-2-ylsulfanyl)acetohydrazide - Cong, Nguyen Tien; Hung, Mai Anh; Nam, Pham Ngoc; Kim Loan, Nguyen Thi (Vietnam Journal of Chemistry, 2014)
Treatment of (4,6-dimethylpyrimidin-2-ylsulfanyl)acetohydrazide with carbon disulfide in the solution of potassium hydroxide in ethanol gave 5,7-dimethyl-[1,2,4]triazolo[1,5-a]pyrimidine-2-thiol not 5-[(4,6-dimethylpyrimidin-2-ylsulfanyl)methyl]-1,3,4-oxadiazole-2-thiol due to the occurrence of a complex mechanism. 5,7-Dimethyl-[1,2,4]triazolo[1,5-a]pyrimidine-2-thiol was transformed into six N-substituted amide derivatives by reaction with different chloroacetamides. The structures of all products were confirmed by IR, NMR, and MS data. Keywords: [1,2,4]triazolo[1,5-a]pyrimidine-2-thiol, amide, (4,6-dimethylpyrimidin-2-ylsulfanyl)acetohydrazide